Analysis Of Ib Working Capital Product Marketing Strategies (Case Study: Bank Jateng Syariah) - Ma'ruf, Aminudin; Tri Nur Alfifa; Aminah Hasyim (Universitas Muhammadiyah Surabaya, 2023)
This study aims to determine the marketing strategy of iB Working Capital products at Bank Jateng Syariah to find out the target market of iB Working Capital products and to determine the level of customer interest. This type of research is field research conducted using qualitative research. The study obtains data using observation, interview, and documentation methods. This research was conducted at Bank Jateng Syariah, Kartasura District, Sukoharjo Regency. The data sources used are primary data and secondary data. The data analysis technique used is a qualitative descriptive type using a deductive mindset, namely by comparing theory with catalytic events from the field. The result of this study is that the marketing strategy applied to the Working Capital iB product at Bank Jateng Syariah is a marketing mix consisting of products, places, promotions, people, and processes (5P) this shows a significant positive influence in increasing customer interest or the general public. Improving marketing strategies for the better provides socialization around rural areas where the dominant community may not yet understand Islamic banking and its products. This research is expected to put forward research implications that may be beneficial for the bank and society. Optimizing the role of Islamic financial institutions in the implementation of working capital iB.